Complementary and integrative medicine perspectives among veteran patients and VHA healthcare providers for the treatment of headache disorders: a qualitative study - Deena E. Kuruvilla; Hayley Lindsey; Amy S. Grinberg; Roberta E. Goldman; Samantha Riley; Sean Baird; Brenda T. Fenton; Jason J. Sico; Teresa M. Damush (BMC, 2022)
Abstract Objective To evaluate veteran patient and provider perceptions and preferences on complementary and integrative medicine (CIM) for headache management. Background The Veterans Health Administration (VHA) has spearheaded a Whole Health system of care focusing on CIM-based care for veteran patients. Less is known about patients' and providers' CIM perceptions and preferences for chronic headache management. Methods We conducted semi-structured interviews with 20 veteran patients diagnosed with headache and 43 clinical providers, across 12 VHA Headache Centers of Excellence (HCoE), from January 2019 to March 2020. We conducted thematic and case comparative analyses. Results Veteran patients and VHA clinical providers viewed CIM favorably for the treatment of chronic headache. Specific barriers to CIM approaches included: (1) A lack of personnel specialized in specific CIM approaches for timely access, and (2) variation in patient perceptions and responses to CIM treatment efficacy for headache management. Conclusion Veteran patients and VHA clinical providers in this study viewed CIM favorably as a safe addition to mainstream headache treatments. Advantages to CIM include favorable adverse effect profiles and patient autonomy over the treatment. By adding more CIM providers and resources throughout the VHA, CIM modalities may be recommended more routinely in the management of veterans with headache.